Go Green School Workshop: Program Pemberdayaan Masyarakat Di SD Negeri 3 Bedali Kediri Jawa Timur - Amik Nadziroh; Zidna Ilma Wahdana; Nuril Kusuma Wardani`; Sabiq Makhzum Zen; Affan Syahru Fauzan (Pusmedia Group Indonesia, 2025)
The increasingly complex environmental issues demand real efforts to instill environmental awareness and caring character from an early age. Elementary schools play a crucial role as a medium for shaping environmentally friendly behavior through practical and educational activities. Based on this premise, this Student Creativity Program for Community Service (PKM) was conducted at SDN 3 Bedali Kediri East Java with the aim of fostering students’ environmental awareness through an interactive and experiential Tree Planting Workshop. The method used in this program was the Community Action Empowerment Approach, which emphasizes collaboration among university students, teachers, and pupils throughout the entire process. This approach consists of several stages, including socialization, training, tree planting practice, and evaluation of the outcomes. Through this method, students were not only provided with theoretical knowledge about the importance of ecosystems and reforestation but were also actively involved in planting and maintaining trees within the school environment. The results indicated improvements in three main aspects: (1) the cognitive aspect, referring to an increased understanding of the ecological functions of plants; (2) the affective aspect, reflected in the growth of empathy, responsibility, and environmental concern; and (3) the psychomotor aspect, represented by the students’ improved skills in planting and caring for trees. Overall, this program demonstrates that character education based on real actions through the Community Action Empowerment Approach is effective in fostering environmental awareness among elementary school students. Through this initiative, SDN 3 Bedali Kediri East Java not only became a greener school but also nurtured a young generation that behaves ecologically and is ready to become responsible agents of change for their environment. Keywords : Workshop; Environmental Education; Participatory Assistance; Go Green.